Accelerator for blast furnace slag-containing cement, spray material, and sprayed concrete

A quick-setting agent for blast furnace slag-containing cement, composed of calcium aluminate, sodium silicate, and sodium carbonate, addresses the issues of short-term strength and hexavalent chromium elution, achieving rapid setting and suppression of chromium leaching.

JP2025006401APending Publication Date: 2025-01-17DENKA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023107183
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Blast furnace cement faces challenges in achieving short-term strength development and there is a concern about hexavalent chromium elution when combined with quick setting agents.

Method used

A quick-setting agent for blast furnace slag-containing cement is formulated with calcium aluminate, sodium silicate, and sodium carbonate in specific mass ratios to enhance short-term strength and suppress hexavalent chromium elution.

Benefits of technology

The solution provides excellent short-term strength development and effectively suppresses hexavalent chromium elution, ensuring rapid setting properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025006401000001
    Figure 2025006401000001
  • Figure 2025006401000002
    Figure 2025006401000002
  • Figure 2025006401000003
    Figure 2025006401000003
Patent Text Reader

Abstract

To provide an accelerator for blast furnace slag-containing cement that offers superior early strength development and rapid setting, effectively reducing the leaching of hexavalent chromium.SOLUTION: An accelerator for blast furnace slag-containing cement is used together with blast furnace slag-containing cement. The accelerator contains calcium aluminate, sodium silicate and sodium carbonate. The mass ratio of the blast furnace slag to the sodium silicate is 15-1,000, and the mass ratio of the blast furnace slag to the sodium carbonate is 15-1,000.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a blast furnace slag-containing cement quick-setting admixture, a spraying material, and a sprayed concrete. [Background technology]

[0002] Conventionally, in tunnel excavation, a method of spraying quick-setting concrete, in which a quick-setting agent is mixed into concrete, has been used to prevent the collapse of exposed natural ground. In this method, materials are measured and mixed in a measuring plant installed at the excavation site to prepare the shotcrete, which is then pumped and mixed with the quick-setting agent pumped from the other side of the junction pipe, and the concrete is sprayed onto the natural ground until it reaches a specified thickness.

[0003] As quick-setting admixtures, there have been proposed a liquid quick-setting admixture comprising a combination of a fluoride-containing water-soluble aluminum complex obtained by the reaction of aluminum sulfate with hydrofluoric acid, aluminum hydroxide, and phosphorous acid and / or an organic acid salt thereof (see Patent Document 1); a concrete quick-setting admixture containing at least one selected from the group consisting of aluminum fluoride, an acidic or basic solution of aluminum, lithium silicate, and lithium aluminate (see Patent Document 2); and a liquid quick-setting admixture comprising a fluoride-containing water-soluble aluminum salt obtained by the reaction of aluminum sulfate with hydrofluoric acid, aluminum hydroxide, and lithium hydroxide, lithium carbonate, lithium sulfate, or the like (see Patent Document 3).

[0004] On the other hand, in recent years, there has been a demand to reduce the amount of cement used in order to reduce carbon dioxide emissions, and the use of by-products such as blast furnace cement has been considered. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2006-193388 A [Patent Document 2] JP 2001-130935 A [Patent Document 3] JP 2005-89276 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, blast furnace cement has the problem that it is difficult to obtain short-term strength, and there is also concern that hexavalent chromium may leach out depending on the combination with the accelerator used.

[0007] In view of the above, an object of the present invention is to provide an accelerator for blast furnace slag-containing cement that is excellent in short-term strength development and quick-setting properties and can suppress the elution of hexavalent chromium. [Means for solving the problem]

[0008] As a result of intensive research conducted by the inventors in light of the above problems, they found that a blast furnace slag-containing cement quick-setting admixture containing calcium aluminate, sodium silicate, and sodium carbonate in a specific ratio can solve the above problems, and thus completed the present invention.

[0009] [1] A quick-setting admixture for blast-furnace slag-containing cement to be used together with cement containing blast-furnace slag, the quick-setting admixture for blast-furnace slag-containing cement containing calcium aluminate, sodium silicate and sodium carbonate, wherein the mass ratio of the blast-furnace slag to the sodium silicate is 15 to 1,000, and the mass ratio of the blast-furnace slag to the sodium carbonate is 15 to 1,000. [2] The blast furnace slag-containing cement quick-setting admixture according to the above [1], wherein the calcium aluminate content is 70 to 99.5 mass %. [3] A spraying material containing the blast furnace slag-containing cement quick-setting admixture described in [1] or [2] above and blast furnace cement. [4] The spraying material according to the above [3], wherein the amount of blast furnace slag in the blast furnace cement is 30 to 90 mass %. [5] Shotcrete containing the spraying material described in [3] or [4] above. Effect of the Invention

[0010] According to the present invention, it is possible to provide an accelerator for cement containing blast furnace slag, which is excellent in short-term strength development and quick-setting property and can suppress elution of hexavalent chromium. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention (the present embodiment) will be described in detail, but the present invention is not limited to the embodiment. In addition, "%" in this specification is based on mass unless otherwise specified.

[0012] [Accelerating agent for cement containing blast furnace slag] The quick-setting admixture for blast-furnace slag-containing cement according to this embodiment is a quick-setting admixture for blast-furnace slag-containing cement used together with cement containing blast-furnace slag, and contains calcium aluminate, sodium silicate, and sodium carbonate, in which the mass ratio of the blast-furnace slag to the sodium silicate is 15 to 1,000, and the mass ratio of the blast-furnace slag to the sodium carbonate is 15 to 1,000.

[0013] The blast furnace slag-containing cement quick-setting admixture according to this embodiment contains calcium aluminate. Calcium aluminate is a mixture of CaO and Al 2 O 3 It is a general term for compounds that have hydration activity and are mainly composed of CaO and / or Al. 2 O 3 Compounds in which a part of the above has been replaced with alkali metal oxides, alkaline earth metal oxides, silicon oxide, titanium oxide, iron oxide, alkali metal halides, alkaline earth metal halides, alkali metal sulfates, and alkaline earth metal sulfates, etc., or CaO and Al 2 O 3 It is a substance mainly composed of these and a small amount of these in solid solution, and calcium aluminate may be either crystalline or amorphous.

[0014] As a specific example of a crystalline substance, CaO is C, Al 2 O 3 A, R 2 O(Na 2 OK 2 O, Li 2 O) is R, then C 3 A and C with alkali metals dissolved therein 14 RA 5 , C.A., C. 12 A 7 Or C 11 A 7 ·CaF 2 , C 4 A Fe 2 O 3 , and C 3 A 3 ·CaSO 4 Among them, amorphous calcium aluminate is preferred because of its good quick setting property. In the case of amorphous calcium aluminate, the vitrification rate is preferably 80% or more.

[0015] The calcium aluminate content in the blast furnace slag-containing cement quick-setting admixture is preferably 70 to 99.5 mass%, more preferably 78 to 98 mass%, and even more preferably 85 to 95 mass%. When the calcium aluminate content is within the above range, it is easy to achieve better short-term strength development and quick-setting properties.

[0016] Calcium Aluminate CaO / Al 2 O 3 The molar ratio is not particularly limited, but from the viewpoint of short-term strength development and suppression of elution of hexavalent chromium, the molar ratio is preferably from 1.3 to 3.0, and more preferably from 1.6 to 2.7.

[0017] The method of obtaining calcium aluminate is to use CaO raw materials such as calcium carbonate and calcium hydroxide, and Al raw materials such as bauxite. 2 O 3For example, the raw materials are mixed in a predetermined ratio, heated and melted in an electric furnace, and then quenched by contacting with compressed air or water. By adjusting the ratio of each raw material, the above CaO / Al 2 O 3 The molar ratio can be adjusted, and the vitrification rate can be adjusted by the temperature during heating and melting and the cooling method.

[0018] When calcium aluminate is obtained industrially, it may contain impurities. Specific examples of impurities include, for example, SiO 2 , Fe 2 O 3 , MgO, TiO 2 , MnO, Na 2 OK 2 O, Li 2 O, S, P 2 O 5 However, the presence of these impurities is not particularly problematic as long as it does not substantially impair the object of the present invention. Specifically, it is not particularly problematic when the total amount of these impurities is 10% or less.

[0019] The Blaine specific surface area value (Blaine value) of calcium aluminate is not particularly limited, but is usually 3,000 to 9,000 cm 2 / g is preferable, and 4,000 to 8,000 cm 2 / g is more preferable. By having the Blaine value within the above range, the handleability can be improved. The Blaine specific surface area value is measured based on the specific surface area test specified in JIS R 5201:2015 "Physical Testing Methods for Cement".

[0020] The blast furnace slag-containing cement quick-setting admixture according to the present embodiment can improve short-term strength development and suppress hexavalent chromium elution by setting the content of sodium silicate in the cement used together with the blast furnace slag-containing cement quick-setting admixture to a specific range of mass ratio. The mass ratio of blast furnace slag to sodium silicate is 15 to 1,000, preferably 20 to 900, more preferably 50 to 700, and even more preferably 100 to 500. If the mass ratio of blast furnace slag to sodium silicate is less than 15, the setting time may be extended and the short-term strength at 10 minutes may decrease, and if it exceeds 1,000, the setting properties and short-term strength at 10 minutes or 30 minutes may decrease and the amount of hexavalent chromium elution may increase.

[0021] The blast furnace slag-containing cement quick-setting admixture according to this embodiment contains sodium silicate. The Blaine value of sodium silicate is 100 to 3000 cm 2 / g is preferred, and 200 to 2000 cm 2 When the Blaine value is within the above range, the initial setting time can be improved.

[0022] The content of sodium silicate in the blast furnace slag-containing cement quick-setting admixture is preferably 0.5 to 40 mass%, more preferably 1.0 to 30 mass%, and even more preferably 1.5 to 15 mass%. When the content of sodium silicate is within the above range, it is easy to suppress the generation of hydrogen sulfide gas and the elution of hexavalent chromium.

[0023] The blast furnace slag-containing cement quick-setting admixture according to the present embodiment can improve short-term strength development and suppress hexavalent chromium elution by setting the content of sodium carbonate and the mass ratio of blast furnace slag to sodium carbonate in the cement used together with the blast furnace slag-containing cement quick-setting admixture to a specific range. The mass ratio of blast furnace slag to sodium carbonate is 15 to 1,000, preferably 20 to 900, more preferably 50 to 700, and even more preferably 100 to 500. If the mass ratio of blast furnace slag to sodium carbonate is less than 15, the setting time may be extended, and if it exceeds 1,000, the setting time may be extended and the 10-minute strength may be reduced.

[0024] The blast furnace slag-containing cement quick-setting admixture according to this embodiment contains sodium carbonate. The Blaine value of sodium carbonate is 100 to 3,000 cm 2 / g is preferable, and 300 to 2,000 cm 2 When the Blaine value is within the above range, the setting time is shortened and the 10-minute strength is increased, so that the amount of hexavalent chromium eluted can be reduced.

[0025] The content of sodium carbonate in the blast furnace slag-containing cement quick-setting admixture is preferably 0.1 to 40 mass%, more preferably 0.5 to 35 mass%, and even more preferably 1 to 30 mass%. When the content of sodium silicate is within the above range, it is easy to suppress the generation of hydrogen sulfide gas and the elution of hexavalent chromium.

[0026] The mass ratio of sodium silicate to sodium carbonate (sodium silicate / sodium carbonate) is preferably 0.02 to 60, more preferably 0.05 to 55, and further preferably 0.1 to 50. When the mass ratio of sodium silicate to sodium carbonate is within the above range, short-term strength development and quick-setting property are easily improved, and elution of hexavalent chromium is easily suppressed.

[0027] The total amount of sodium silicate and sodium carbonate in the blast furnace slag-containing cement quick-setting admixture is preferably 2 to 40 mass%, more preferably 5 to 35 mass%, and even more preferably 10 to 30 mass%. When the total amount of sodium silicate and sodium carbonate is within the above range, short-term strength development and quick-setting properties are easily improved, and elution of hexavalent chromium is easily suppressed.

[0028] [Spraying material] The spraying material according to the present embodiment contains the quick-setting admixture for blast-furnace slag-containing cement of the present invention and blast-furnace cement. By containing the quick-setting admixture for blast-furnace slag-containing cement and blast-furnace cement, the spraying material is excellent in short-term strength development and quick-setting properties, and can suppress hexavalent chromium elution. Note that the blast-furnace cement in the present invention is blast-furnace cement defined in JIS R 5211:2009 "Blast-furnace cement" or blast-furnace cement obtained by mixing blast-furnace slag with ordinary portland cement or the like, and containing blast-furnace slag in an amount equal to or greater than the amount defined in the above JIS.

[0029] The content of the quick-setting admixture for blast-furnace slag-containing cement in the spraying material is preferably 3 to 20 parts by mass, more preferably 5 to 15 parts by mass, per 100 parts by mass of blast-furnace cement. By having the content of the quick-setting admixture for blast-furnace slag-containing cement within the above range, it is easy to achieve excellent short-term strength development and quick setting properties, and it is easy to suppress the elution of hexavalent chromium.

[0030] The amount of blast furnace slag in the blast furnace cement is preferably 30 to 90 mass %, more preferably 40 to 70 mass %. When the amount of blast furnace slag is within the above range, it is easy to suppress the elution of hexavalent chromium.

[0031] [Shocked concrete] The sprayed concrete according to the present embodiment contains the sprayed material of the present invention. The sprayed concrete can be obtained by mixing the sprayed material with water and spraying the mixture, and has excellent short-term strength development and quick-setting properties and can suppress elution of hexavalent chromium.

[0032] The content of the spraying material in the shotcrete is preferably 10 to 30 mass%, more preferably 15 to 25 mass%. When the content of the spraying material is within the above range, it is easy to achieve excellent short-term strength development and quick setting, and it is easy to suppress the elution of hexavalent chromium.

[0033] The water-cement ratio of the sprayed concrete is preferably 30 to 70%, more preferably 40 to 60%, based on the blast-furnace cement in the sprayed material. By having the water-cement ratio within the above range, it is easy to achieve excellent short-term strength development and quick setting, and it is easy to suppress the elution of hexavalent chromium.

[0034] In practice, sprayed concrete uses aggregate, but the aggregate is not particularly limited, and preferably has low water absorption and high aggregate strength. The maximum size of the aggregate is not particularly limited as long as it can be sprayed. River sand, mountain sand, sea sand, lime sand, and silica sand can be used as fine aggregate, and river gravel, mountain gravel, and lime gravel can be used as coarse aggregate, and crushed sand and crushed stone can also be used.

[0035] The content of aggregate in the shotcrete is preferably 60 to 80 mass %, and more preferably 65 to 75 mass %. EXAMPLES

[0036] The present invention will be described in more detail below using examples and comparative examples. However, the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention.

[0037] [Experimental Example 1] <Preparation of Accelerator for Cement Containing Blast Furnace Slag> The materials shown below were mixed in the ratios shown in Table 1 to prepare an accelerator for blast-furnace slag cement.

[0038] <Materials used> Calcium aluminate: CaO / Al 2 O 3Amorphous calcium aluminate was prepared by melting calcium carbonate and aluminum oxide in an electric furnace and quenching them to obtain a molar ratio of 2.3. The vitrification rate was 97% (measured by powder X-ray diffraction) and the Blaine value was 5,800 cm. 2 / g, amorphous. Sodium silicate: Sodium metasilicate, powder, Blaine value: 1,280 cm 2 / g Sodium carbonate: powder, Blaine value 1,100 cm 2 / g.

[0039] <Preparation of spraying materials> As the blast furnace slag-containing cement, 400g of ordinary Portland cement (manufactured by Denka Co., Ltd.) and 400g of ground blast furnace slag (manufactured by Esment Kanto Co., Ltd.: product name Esment 4000) were mixed to prepare blast furnace cement (blast furnace slag content 50% by mass). 2,000g of fine aggregate (river sand from the Hime River water system in Niigata Prefecture) and water were added to give a water-cement ratio of 50%, and the mixture was kneaded. 10 parts by mass of the prepared blast furnace cement quick-setting admixture was added per 100 parts by mass of the blast furnace cement to prepare the spraying material.

[0040] <Coagulation test> The prepared spray material was quickly sprayed onto a formwork measuring 30 cm in length, 30 cm in width, and 10 cm in depth, and the Proctor penetration resistance was measured over time from the addition of the accelerator, reaching 3.5 N / mm 2 The time when this occurs is the starting time, 28.0N / mm 2 The time when the reaction time reached the end was determined as the termination time. The results are shown in Table 1 below.

[0041] <Compressive strength test> The prepared spray material was quickly sprayed onto a triple-section formwork measuring 4 cm length x 4 cm width x 16 cm depth, and the compressive strength was measured at 10 minutes, 30 minutes, 24 hours, and 3 days after the addition of the quick-setting admixture. The results are shown in Table 1. In the present invention, the compressive strengths at 10 minutes, 30 minutes, 24 hours, and 3 days are indicators of short-term strength, and the compressive strength at 28 days is an indicator of long-term strength.

[0042] <Amount of eluted hexavalent chromium> The prepared spraying material was quickly sprayed onto the formwork after preparation, and the amount of hexavalent chromium eluted was measured for the sprayed concrete at ages of 3.5 hours and 3 days depending on the time elapsed since the addition of the accelerator, based on the method specified in "Elution test conducted at the mix design stage, Environment Agency Notification No. 46" dated August 23, 1991. The results are shown in Table 1.

[0043] <Amount of hydrogen sulfide gas generated> In a 20℃ environment, 100g of blast furnace cement and 50g of water were added to a vinyl bag measuring 340mm long x 230mm wide to prepare a cement paste, and after 1 minute, 10g of the prepared blast furnace cement accelerator was added and the bag was closed. After 10 minutes, 1mL of gas was collected from the bag and the amount of hydrogen sulfide gas was quantified using gas chromatography. The results are shown in Table 1.

[0044] [Table 1]

[0045] [Experimental Example 2] Each test was carried out in the same manner as in Experimental Example 1, except that aluminum sulfate (aluminum sulfate 14-18 hydrate, purity 98%, industrial raw material) was used in addition to the materials used in Experimental Example 1. The results are shown in Table 2.

[0046] [Table 2]

[0047] [Experimental Example 3] Each test was carried out in the same manner as in Experimental Example 1, except that the content of blast furnace slag in the blast furnace cement prepared as the blast furnace slag-containing cement was changed to the value shown in Table 2, and the same materials as in Experimental Example 1 were mixed in the ratios shown in Table 2 to prepare the quick-setting admixture for blast furnace slag-containing cement. The results are shown in Table 3.

[0048] [Table 3] [Industrial Applicability]

[0049] The blast furnace slag-containing cement quick-setting admixture of the present invention can be suitably used for cement concrete to be sprayed onto exposed natural ground surfaces such as tunnels for roads, railways, and waterways, and slopes.

Claims

1. A blast furnace slag-containing cement accelerator for use with a cement containing blast furnace slag, comprising: Contains calcium aluminate, sodium silicate and sodium carbonate, The mass ratio of the blast furnace slag to the sodium silicate is 15 to 1,000; A blast furnace slag-containing cement quick-setting admixture, wherein the mass ratio of the blast furnace slag to the sodium carbonate is 15 to 1,000.

2. The blast furnace slag-containing cement quick-setting admixture according to claim 1, wherein the calcium aluminate content is 70 to 99.5 mass%.

3. A spraying material comprising the blast furnace slag-containing cement quick-setting admixture according to claim 1 or 2 and blast furnace cement.

4. The spraying material according to claim 3, wherein the amount of blast furnace slag in the blast furnace cement is 30 to 90 mass%.

5. A sprayed concrete comprising the sprayed material according to claim 4.

Citation Information

Patent Citations

  • Rapidly curing agent for concrete

    JP2001130935A

  • Liquid quick setting admixture

    JP2005089276A

  • Liquid quick-setting agent

    JP2006193388A